Formulation and characterization of coconut coir surfactant containing lignosulfonates for enhanced oil recovery - Norhisyam Ismail, 1986- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Thesis (Sarjana Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2012